Survival and success of implants in a private periodontal practice: a 10 year retrospective study - Bäumer, Amelie; Toekan, Shirin; Saure, Daniel; Körner, Gerd (BMC oral health, 2020)
To assess long-term results of implants (XiVE/Frialit-2 Synchro) in a private periodontal practice according to survival and success rates (biological and technical complications) and to detect possible influencing factors, retrospectively.